What Do Group Members Share? The Privileged Status of Cultural Knowledge for Children. Issue 10 (19th September 2019) - Soley, Gaye
Abstract : Abstract: An essential aspect of forming representations of social groups is to recognize socially relevant attributes licensed by the group membership. Because knowledge of cultural practices tends to be transmitted through social contact within social groups, it is one of the fundamental attributes shared among members of a social group. Two experiments explored whether 5‐ and 6‐year‐olds selectively attribute shared cultural knowledge on the basis of group membership of agents. Using novel social groups, children were introduced to one target agent and two other agents, one of which belonged to the same group as the target and one belonged to a different group. Children were then asked who would know or like same things as the target agent. The results showed that children expect group members to know the same songs, whereas they do not necessarily expect them to like the same songs or know the same generic facts. These findings suggest that children are remarkably selective in the attributions they make based on social group membership and from early on, they expect social group membership and cultural knowledge to be closely linked.